Group B Streptococcus Serotypes in Pregnant Women From the Western Cape Region of South Africa - Africa, Charlene W. J.; Kaambo, Eveline (Frontiers in Public Health, 2018)
Background: Maternal colonization of Group B streptococci (GBS) during pregnancy is an important risk factor for neonatal morbidity and mortality. The aim of this study was to determine the prevalence and serotype distribution of GBS isolated from a cohort of pregnant women in the Western Cape, South Africa. Methods: Two ano-vaginal swabs were collected from 301 women at 28–37 weeks of gestation. Participants were recruited from four different antenatal clinics in the Western Cape, South Africa. GBS were detected by culture and PCR and serotypes confirmed by latex agglutination tests. Antibiotic sensitivity was performed using disc diffusion. Results: The GBS colonization rate was 16.6%. Serotype distribution revealed serotype V as the predominant serotype (66.67%) followed by serotype III (21.05%). Serotypes Ia, II, IV, and IX constituted 1.75% each and 3 GBS isolates were non-typeable. Serotype V demonstrated resistance to most of the antibiotics tested, while serotype III demonstrated better susceptibility, except for tetracycline. No significant differences were observed for GBS colonization or serotype distribution according to HIV status. Conclusion: Predominating serotypes differed from those previously reported from other regions in South Africa. Global surveillance of serotype distribution plays an important role in informing vaccine development and antibiotic prophylaxis.